A comparison of lateral internal sphincterotomy versus subcutaneous fissurectomy under local anaesthesia with 2% diltiazem gel in the management of chronic fissure in ano: prospective study - Shukla, Arvind; Brahmane, Abhay; S., Yogesh H.; P., Kovarthanan (International Surgery Journal, 2022)
Background: Anal fissure is one of the most common benign anorectal condition that is caused by an ulcer or breach in the anoderm of the anal canal. It causes very severe pain and discomfort and directly affects the quality of life. From the past, various surgical treatment modalities have been practised to bring complete cure and relief but have always been associated with secondary complications. The aim of the study was to compare efficacy of outcome of lateral internal sphincterotomy and subcutaneous fissurectomy with topical 2% diltiazem gel in the treatment of chronic fissure in ano. Methods: 60 patients who were diagnosed with chronic anal fissure between 2019-2021 at MGM Medical College were undertaken in this study. Patients were selected randomly on alternate basis. Group A patients were subjected to subcutaneous fissurectomy under local anaesthesia with post-operative application of 2% diltiazem gel. Group B patients were subjected to LIS. Surgical wound infection, absenteeism from work, symptomatic relief were assessed and compared between the groups. Results: There was no significant difference among both the study population in terms of age and gender. There was a statistically significant association between post-operative wound infection (p=0.011), number of work days lost (p=0.008) and satisfaction level (p=0.020). Conclusions: LIS is still a better surgical choice for treating chronic anal fissures than subcutaneous fissurectomy with 2% diltazem gel, due to less complications, faster pain alleviation, and fewer missed work days.